Design and application of a monitoring device for embedded foundation side friction resistance - Tian, Wei; Chen, Peishuai; Li, Jiacheng; Ji, Fuquan (Frontiers in Earth Science, 2024)
The magnitude and distribution of side friction resistance (SFR) is the basis for embedded foundation design and construction method selection. However, there is no technique to directly measure the SFR. To further understand distribution law of the SFR, this paper developed a monitoring device that can directly measure the SFR. A theoretical conversion formula for the elastic deformation and the SFR that considers the end effect of sensor sealing was proposed to guide the selection of sensor size and sealing material. The monitoring device for the SFR was then calibrated using a large-scale direct shear apparatus. The losses of sensitivity coefficient before and after sealing were analyzed, and the calibration coefficient of the sensor was adjusted accordingly. The calibration results revealed that under cyclic loading and unloading conditions, the linear correlation coefficient of the sensor was greater than 0.996, and the sensitivity after sealing could reach 4.836 με/kPa, which met requirements of the engineering application. The developed monitoring device characterized by simple testing principle, low cost, and high precision were successfully applied to an open caisson project in Harbin City, which contributes to address the difficult problem of efficiently collecting the SFR in highways, bridges, water conservancy, and other projects.